PENILAIAN UJI TROPONIN I DENGAN POINT OF CARE TESTING - Sheila Febriana; Asvin Nurulita; Uleng Bahrun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2016)
Troponin I is a cardiac biomarker recomended by The Third Global Myocardial Infarction Task Force World Health Organisation(WHO). Troponin plays a central role as a relevant biomarker that require reliable samples, methods, device and efficiency of time.Selecting the device, methods and sample used in the assay may affect the results and turn arround time. The aim of this study is toknow troponin I result using Point of care Testing device with a flourescence immunoassay methods using whole blood and laboratorybasedanalysis device with Enzyme-Linked Fluorescent Assay (ELFA) methods using serum by evaluation. Cross sectional study was heldon 50 subjects in Wahidin Sudirohusodo hospital during the period between July-August 2015, those who suspected suffering acutecoronary syndome (ACS) and underwent troponin I test ordered by the physician and also had whole blood sample. The subjects arearound 51.96±12.80 year old and most of them are men (62%). The mean consentration of troponin I with laboratoric-based analysis is0.50±1.69 μg/L and with POCT is 0.51±1.77. The Pearson correlation test shows the correlation (r) is 0.99 with the p value is <0.001.Bland and Altman methods show the mean difference between two assays is 0.014μg/L (95% confidence interval, -0.015; 0.043) withthe limit of agreement -0.19 to 0.22. Based on this study, it can be concluded that troponin I assay using POCT device can be used tosupport ACS diagnosis precisely and rapidly. It is suggested to perform futher study with concern on the patient’s clinical condition aswell as the diagnosis, so it can evaluate the device performance to measure troponin I levels consistently with the clinical condition.